Southeast Inka Frontiers : Boundaries and Interactions - Alconini Mujica, Sonia (Book collections on Project MUSE., 2016)
Alconini explores the interactions between the Inka and Amazonia, a large empire versus a less complex population. The book focuses on frontier archaeology and the socio-economic forces at play in the Inka empire's borders.